Community Physics Website Designing Using PHP, Macromedia Dreamweaver MX 2004 and MySQL - Abrar Nasbey; Rahayu Noveandini, SKom, MM (Jurnal Sistem Informasi, 2007)
Physics is a subject familiar among High School students. View of development, lack of interest to physics students, because it was considered less interesting and boring. To the authors intend to introduce physics via a WebSite. Where, students who are able to search for Surfer and obtain various types of information related to physics and can join the physics community to the interaction among members of the physics community.